2001
DOI: 10.1111/j.1365-2621.2001.tb15200.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Extractability of Calcium, Iron, and Zinc in Finger Millet and Kidney Beans During Processing

Abstract: Finger millet (Eleusine coracana) and kidney beans (Phaseolus vulgaris) were processed by soaking, germination, autoclaving, and fermentation for incorporation into a complementary food for children. Extractability of calcium, iron, and zinc were determined by in vitro HCl-Pepsin and Pepsin-Pancreatin methods after each processing step. Germination significantly increased the in vitro extractability of these minerals, while soaking, autoclaving and fermentation showed a smaller or insignificant effect. Iron ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 26 publications
4
47
2
Order By: Relevance
“…For dietary fiber, in vivo studies have found that the addition of cereal fiber to human and animal diets has consistently depressed absorption and retention of calcium (Knox et al, 1991). The findings on the effect of phytate and fiber on calcium bioavailability in this study was in agreement with numerous studies both in vivo Weaver et al, 1993;Hansen et al, 1996;Younes et al, 1996;Levrat-Verny et al, 1999) and in vitro (Benway and Weaver, 1993;Dyck et al, 1996;Bosscher et al, 1998;Lombardi-Boccia et al, 1998;Lucarini et al, 1999;Kennefick and Cashman, 2000;Mamiro et al, 2001). Therefore, the presence of food components high in phytate and dietary fiber such as whole meal flour and oatmeal can act as inhibitors on calcium bioavailability.…”
Section: Resultssupporting
confidence: 93%
“…For dietary fiber, in vivo studies have found that the addition of cereal fiber to human and animal diets has consistently depressed absorption and retention of calcium (Knox et al, 1991). The findings on the effect of phytate and fiber on calcium bioavailability in this study was in agreement with numerous studies both in vivo Weaver et al, 1993;Hansen et al, 1996;Younes et al, 1996;Levrat-Verny et al, 1999) and in vitro (Benway and Weaver, 1993;Dyck et al, 1996;Bosscher et al, 1998;Lombardi-Boccia et al, 1998;Lucarini et al, 1999;Kennefick and Cashman, 2000;Mamiro et al, 2001). Therefore, the presence of food components high in phytate and dietary fiber such as whole meal flour and oatmeal can act as inhibitors on calcium bioavailability.…”
Section: Resultssupporting
confidence: 93%
“…The phytate contents also fell within previously reported ranges for finger millet (242-1310 mg/100 g) (Mamiro et al, 2001;Shashi et al, 2007). The mineral contents fell within the previously reported ranges: Ca (240-532 mg/100 g), Zn (0.9-2.9 mg/100 g), Fe (3.3-20 mg/100 g), P (130-325 mg/100 g) and Mg (66-183 mg/100 g) (Ravindran, 1991;Mamiro et al, 2001;Shashi et al, 2007;Glew et al, 2008;Shobana et al, 2012). PIXE analysis did not reveal any significant aluminium contents or patterns (results not shown).…”
supporting
confidence: 89%
“…It is speculated that this enzyme plays a role in phytate hydrolysis in the gastrointestinal tract and therefore its activity should be retained even after processing (Lopez, Leenhardt, Coudray, & Remesy, 2002). Literature research shows that activation of endogenous phytases by germination is one of the most effective ways to reduce phytate in cereals (Sandberg & Svanberg, 1991;Mbithi-Mwikya et al, 2000;Mamiro et al, 2001;Egli et al, 2002). Another effective alternative method involves use of exogenous phytases (Sandberg & Svanberg, 1991;Hurrell, Reddy, Juillerat, & Cook, 2003).…”
Section: Antinutrientsmentioning
confidence: 97%
“…Tannins also complex enzymes of the digestive tract adversely affecting utilization of proteins and carbohydrates and resulting in reduced growth, feeding efficiency, metabolizable energy and bioavailability of amino acids. Traditional artisanal technologies such as decortication, soaking, germination and fermentation of cereal-based foods reduce the levels of tannins and phytates, increase bioavailability of amino acids and mineral elements and improve protein and starch digestibility (Lorri & Svanberg, 1993;Mbithi-Mwikya et al, 2000;Mamiro, van Camp, Mbithi-Mwikya, & Huyghebaert, 2001); but these technologies are limited by their laborious and timedemanding nature. The effect of extrusion cooking on phytic acid has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%